Pemetaan Potensi Alam Taman Sukorejo sebagai Pesona Keindahan Budaya Lokal - Restu Putra, Dean Vernanda; Misbahuddin, Muhammad; Fitriawan, Fuad (Social Science Academic, 2024)
This study aims to explore and optimize the natural potential of Sukorejo Village as a tourist attraction that can enrich the local cultural beauty. The main objective is to develop effective strategies to promote Sukorejo Village as a nature and culture-based tourism destination, as well as to raise public awareness of the importance of environmental preservation and cultural heritage. ABCD Method: - Audience: This research targets the community of Sukorejo Village, potential tourists, as well as local government and academics interested in sustainable tourism development; - Behavior: The study analyzes the behavior of the local community in preserving natural and cultural potential, as well as how tourists and the government respond to the tourist attractions of Sukorejo Village; - Condition: The research is conducted within the context of limited infrastructure, varying levels of awareness, and natural and cultural potential that has not been fully utilized;- Degree: This study aims to increase tourist visits and public awareness, as well as to encourage policy changes for better tourism infrastructure development. The study found that Sukorejo Village has significant natural potential, including beautiful landscapes and rich cultural heritage. However, challenges in infrastructure and promotion remain major obstacles. With the right strategies, Sukorejo Village has great potential to develop as a leading tourist destination that combines natural beauty and cultural richness. This abstract provides a brief overview of the objectives, ABCD method, and results of the research, which is expected to make a significant contribution to the development of Sukorejo Village's tourism potential.